Analisis Volume Lalu Lintas dan Kinerja Jalan Sebagai Indikator Risiko Kegagalan Perkerasan Berbasis Pendekatan DEFMEFA - Adinda Juwita Nasution; Elsa Eka Putri; Masrilayanti Masrilayanti; M. Ridwan Anas (Greenation Publisher & Yayasan Global Resarch National, 2026)
This study is entitled “Analysis of Traffic Volume and Road Performance as Indicators of Pavement Failure Risk Based on the DEFMEFA Approach”, which aims to analyze traffic parameters as traffic loading proxies in identifying pavement failure risks using the Dynamic Engineering Failure Mode and Effect Analysis approach. The research was conducted on the Karya Wisata Road section in Medan City. The analyzed parameters include traffic volume, road capacity, volume-to-capacity ratio, level of service, and side friction.The analysis results indicate a traffic volume of 1,278 passenger car units per hour (pcu/hour) with a road capacity of 1,518 pcu/hour, resulting in a volume-to-capacity ratio of 0.84 and a level of service categorized as D (approaching saturation). The assessment results show that the highest failure risks are permanent deformation (rutting) and fatigue cracking due to the high intensity of traffic loading.This study demonstrates that traffic parameters can be used as an initial approach in pavement failure risk analysis without requiring direct structural data. Therefore, the integration of traffic analysis and the Dynamic Engineering Failure Mode and Effect Analysis approach can support more proactive, targeted, and risk-based decision-making in road preservation.